Ontogeny and colonization of embryonic border-associated macrophages and their role in neurodevelopment - Otero, Ashley M.; Antonson, Adrienne M. (Frontiers in Cellular Neuroscience, 2025)
Border-associated macrophages (BAMs) are tissue-resident macrophages in the central nervous system (CNS) that originate from yolk sac progenitors during primitive hematopoiesis. While much is known about their parenchymal counterparts, microglia, recent evidence indicates that BAMs also play roles in neurodevelopment. Located at CNS interfaces such as the meninges, choroid plexus, and perivascular space, BAMs facilitate immune surveillance, vascular modeling, debris clearance, and cerebrospinal fluid dynamics. Despite their strategic location, BAMs have historically been understudied in developmental contexts. This mini review covers their embryonic origins, regional diversification, and functional roles as development progresses. Offering new insights, we consider BAMs in the context of neurodevelopmental disorders (NDDs). Recent findings from maternal immune activation (MIA) studies suggest that fetal BAMs may contribute to aberrant cortical development through altered inflammatory signaling. We propose that, like microglia, BAMs may play previously unappreciated roles in shaping the developmental trajectory of the brain. To aid future research, we also review current tools for studying BAMs in vivo and in vitro, including new transgenic lines and organoid-based approaches. These tools will be critical for dissecting the molecular functions of BAMs during healthy and disordered development. Understanding BAM biology in early life may reveal novel mechanisms underlying NDDs and inform therapeutic strategies targeting brain–immune interfaces.